2010
DOI: 10.1002/aur.147
|View full text |Cite
|
Sign up to set email alerts
|

Perception of emotion in musical performance in adolescents with autism spectrum disorders

Abstract: Scientific Abstract Individuals with autism spectrum disorders (ASD) are impaired in understanding the emotional undertones of speech, many of which are communicated through prosody. Musical performance also employs a form of prosody to communicate emotion, and the goal of this study was to examine the ability of adolescents with ASD to understand musical emotion. We designed an experiment in which each musical stimulus served as its own control while we varied the emotional expressivity by manipulating timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 102 publications
1
21
0
1
Order By: Relevance
“…Because prior research indicates that music can be effective in conveying basic emotions to persons with ASD, clinicians and researchers have hypothesized that music may be both motivating and effective as a therapeutic tool for improving recognition or expression of emotions, communication, and social skill acquisition (e.g., Allen & Heaton, 2010; Boso, Emanuele, Minazzi, Abbamonte & Politi, 2007; Gold, Wigram, & Elefant, 2006; Heaton, Allen, et al, 2008; Kaplan, 2005; Katagiri, 2009; Molnar-Szakacs, et al, 2009). From a methodological perspective, it is of interest that prior studies may have examined fewer or different categories of emotions (Heaton, Hudry, et al, 2008), or may have measured intensity of emotions (Bhatara et al, 2010); further study of all the basic emotions in relation to the ASD population is of interest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because prior research indicates that music can be effective in conveying basic emotions to persons with ASD, clinicians and researchers have hypothesized that music may be both motivating and effective as a therapeutic tool for improving recognition or expression of emotions, communication, and social skill acquisition (e.g., Allen & Heaton, 2010; Boso, Emanuele, Minazzi, Abbamonte & Politi, 2007; Gold, Wigram, & Elefant, 2006; Heaton, Allen, et al, 2008; Kaplan, 2005; Katagiri, 2009; Molnar-Szakacs, et al, 2009). From a methodological perspective, it is of interest that prior studies may have examined fewer or different categories of emotions (Heaton, Hudry, et al, 2008), or may have measured intensity of emotions (Bhatara et al, 2010); further study of all the basic emotions in relation to the ASD population is of interest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, those with ASC have enhanced accuracy in pitch processing (Heaton, 2003(Heaton, , 2005 and pitch discrimination (Bonnel et al, 2003(Bonnel et al, , 2010. However, adolescents with ASC are less accurate at detecting emotional expressivity in musical performance (Bhatara et al, 2010). Although research has suggested that individuals with ASC do not have deficits in emotional categorization (Quintin, Bhatara, Poissant, Fombonne, & Levitin, 2011), reports of emotional reactivity to music by individuals with ASC are different compared to the general population (Allen, Hill, & Heaton, 2009 (Accordino, Comer, & Heller, 2007).…”
mentioning
confidence: 99%
“…In view of the repeated description of unimodal emotional decoding deficits in depression, anxiety or anorexia nervosa (e.g. Bhatara et al, 2010;Mendlewicz et al, 2005;Rossignol et al, 2005), it would be interesting to explore the evolution of these deficits in crossmodal settings. Indeed, it might be hypothesized that these psychiatric states will lead, as it has been observed in alcoholdependence, to increased deficits in crossmodal stimulations.…”
Section: What Should Be Done In Future Research?mentioning
confidence: 99%